2016
DOI: 10.1155/2016/2583747
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Alterations of Cardiac Mechanics Present Early in the Course of Pediatric Type 1 Diabetes Mellitus: A Prospective Blinded Speckle Tracking Stress Echocardiography Study

Abstract: Diabetic cardiomyopathy substantially accounts for mortality in diabetes mellitus. The pathophysiological mechanism underlying diabetes-associated nonischemic heart failure is poorly understood and clinical data on myocardial mechanics in early stages of diabetes are lacking. In this study we utilize speckle tracking echocardiography combined with physical stress testing in order to evaluate whether left ventricular (LV) myocardial performance is altered early in the course of uncomplicated type 1 diabetes mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
44
2
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 84 publications
6
44
2
4
Order By: Relevance
“…Our study TDI results showed that duration of diabetes had negative impact on the LV diastolic and systolic functions. On the other hand, all pediatric studies using 2DSTE have reported negative correlation between glycemic control and LV strains (LS, CS, and RS) but no correlation between duration of T1DM and LV strains . In the present study, we found negative correlation between duration of T1DM and LV strains which agree with Nakai et al.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our study TDI results showed that duration of diabetes had negative impact on the LV diastolic and systolic functions. On the other hand, all pediatric studies using 2DSTE have reported negative correlation between glycemic control and LV strains (LS, CS, and RS) but no correlation between duration of T1DM and LV strains . In the present study, we found negative correlation between duration of T1DM and LV strains which agree with Nakai et al.…”
Section: Discussionsupporting
confidence: 91%
“…Altun et al reported in addition to diastolic dysfunction, impaired LV longitudinal and radial function (global LS and RS) in asymptomatic children and adolescents with type 1 DM who have normal LV ejection fraction. On the other hand, Hensel et al performed speckle tracking echocardiography in combination with ergometer stress testing in asymptomatic normotensive pediatric patients with uncomplicated T1DM and healthy controls. They found increased circumferential and longitudinal strain rate in T1DM patients both at rest and during exercise test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathophysiology of diabetes associated cardiac impairment is not fully understood yet but can be attributed to suppressed glucose oxidation, impaired calcium homeostasis, high level of oxidative stress, altered intracellular signaling, activation of renin‐angiotensin system, enhanced fatty acid metabolism, cardiac autonomic dysfunction, and pathological remodeling …”
Section: Introductionmentioning
confidence: 99%
“…Recently, two-dimensional speckle tracking echocardiographic studies to demonstrate LV mechanical dysfunction more sensitively and a few studies have published in children with type 1 DM 8)9). Hensel et al10) reported that asymptomatic type 1 DM children had signs of hyperdynamic LV contractility early in the course of the disease. And, poor glycemic control was associated with early subclinical LV systolic and diastolic impairment.…”
mentioning
confidence: 99%